Systematic review of thyroid function in NKX2-1-related disorders: Treatment and follow-up. - Beatriz Carmona-Hidalgo; Estefanía Herrera-Ramos; Rocío Rodríguez-López; Laia Nou-Fontanet; José C Moreno; Juan Antonio Blasco-Amaro; Juliane Léger; Juan Darío Ortigoza-Escobar; NKX2-1-Related Disorders Guideline Working Group (PLoS ONE)
Background NKX2-1, a crucial transcription factor in thyroid, lung, and brain development, is associated with rare disorders featuring thyroid dysfunction, neurological abnormalities, and respiratory symptoms. The primary challenge in managing NKX2-1-related disorders (NKX2-1-RD) is early diagnosis of the genetic defect and treating specific endocrine disorders. Levothyroxine (LT4) serves as the standard hypothyroidism treatment, with required dosages influenced by the severity of the individual's disorder, which varies widely among affected individuals. Objectives This systematic review aims to assess the effectiveness of LT4 treatment in NKX2-1-RD and explore optimal dosing strategies. The primary focus is on the challenges associated with the prompt diagnosis of genetic defects, rather than the established treatment protocols for individual endocrine failures. Methods Adhering to PRISMA guidelines, the review includes 42 studies involving 110 genetically confirmed NKX2-1-RD patients with hypothyroidism. The study investigates congenital hypothyroidism as the most prevalent endocrine alteration, along with gestational and overt hypothyroidism. The administration of LT4 treatment, dosages, and patient responses are analyzed. Results Among the findings, congenital hypothyroidism emerges as the predominant endocrine alteration in 41% of patients. Notably, LT4 treatment is administered in only 10% of cases, with a mean dose of 52 μg/day. The variability in initiation and dosage is likely influenced by the age at diagnosis. Positive responses, characterized by TSH adjustments within normal ranges, are observed in 11 monitored patients. Conclusions Early detection of congenital hypothyroidism is emphasized for timely LT4 initiation. Challenges in standardization are highlighted due to the variability in clinical manifestations and diagnostic procedures across NKX2-1-RD cases. While this review provides valuable insights into thyroid and pituitary disease treatment, limited details on LT4 treatment represent a significant study limitation. Key reporting points for future case studies are proposed to enhance the understanding and management of NKX2-1-RD hypothyroidism.